Palabas at Paloob: Tambalang Mukha ng Pagtula - Almario, Virgilio S. (Philippine Humanities Review; Vol 16 No 1 (2014), 2016)
National Artist for Literature Virgilio S. Almario explains the literary concepts “palabas” and “paloob” first introduced in the 1980s as distinct characteristics of two leading poetic traditions in the country: Balagtasism and Modernism. Almario cites several examples across generations of poets and poetry in order to clarify the intertwined relation between the two. Keywords: palabas, paloob, literary traditions, Balagtasism, Modernism